CLINICAL AND LABORATORY INDICATORS IN CHILDREN WITH URILOSTICAL DISEASE - Berdiyarova Shokhida Shukurullaevna,; Murtazaeva Nasiba Komiljonovna,; Ochilov Sardor Abdugani Ugli, (International Journal of Innovations in Engineering Research and Technology, 2023)
A study was conducted of changes in biochemical parameters in urolithiasis with different types of stone localization and clinical picture. All patients underwent an outpatient examination: a general clinical examination, including a general urine test; biochemical; hematological. The article presents the results of studies of inpatients diagnosed with urolithiasis. These studies are relevant due to the need for constant monitoring of prescribed laboratory tests by clinicians when managing these patients. This allows you to increase the level of competence of specialists in the field of laboratory services and for urologists, improves the rationality of prescribing laboratory tests for various nosologies and work with “Standards of diagnosis and treatment”. It turned out that laboratory test orders for urolithiasis do not always correspond to the standard of medical care.